2021
DOI: 10.1136/jitc-2020-002071
|View full text |Cite
|
Sign up to set email alerts
|

HLA Ligand Atlas: a benign reference of HLA-presented peptides to improve T-cell-based cancer immunotherapy

Abstract: BackgroundThe human leucocyte antigen (HLA) complex controls adaptive immunity by presenting defined fractions of the intracellular and extracellular protein content to immune cells. Understanding the benign HLA ligand repertoire is a prerequisite to define safe T-cell-based immunotherapies against cancer. Due to the poor availability of benign tissues, if available, normal tissue adjacent to the tumor has been used as a benign surrogate when defining tumor-associated antigens. However, this comparison has pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
160
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(173 citation statements)
references
References 68 publications
13
160
0
Order By: Relevance
“…6 ). As seen in the figure, compartment related to extracellular exomes, protein secretions and recycling are highly enriched, which is in agreement with previous findings [ 44 ] and with the biological rule of HLA-II proteins as presenters of endosomal and lysosomal proteins.
Fig.
…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…6 ). As seen in the figure, compartment related to extracellular exomes, protein secretions and recycling are highly enriched, which is in agreement with previous findings [ 44 ] and with the biological rule of HLA-II proteins as presenters of endosomal and lysosomal proteins.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…As a first case study, we started by analyzing data from the HLA-ligand atlas [ 44 ] database using the library. Given that different tissues have different processing capabilities, for example, by expressing different sets of digestive enzymes, we started first by looking at the sequences located upstream and downstream of the identified peptides in their inferred parent proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combined dataset of mass spectrometry raw data of mono-allelic HLA class I peptidomes (399 raw files, 88 HLA alleles) were obtained from two prior studies 8,17 (MSV000080527 and MSV000084172). List of reported antigen-HLA pairs were obtained from the Immune Epitope Database 15 (IEDB, downloaded December 2020), the HLA Ligand Atlas 32 (downloaded June 2020), and from peptidomics analyses of multi-allelic patient samples 8,33 . It should be noted that these recent studies of patient samples not only reported new data but also provided compilations of multi-allelic peptidomics data from earlier studies.…”
Section: Collection Of Published Hla Class I Peptidomics and Antigen Datamentioning
confidence: 99%
“…It is also time as a field that we decide how we debate these issues and in my opinion time to stop subjectively re-searching others data but to design and implement our own experiments to more definitely corroborate or repudiate various sources of antigenic peptides in the immunopeptidome. Our field has made great strides and can look back at great community initiatives: the human immunopeptidome project ( 46 ) that strives to advance the documentation of peptides available for immune recognition in a variety of healthy and diseased states; minimal information requirements for an immunopeptidomics experiment ( 47 ) and HLA peptide atlases ( 48 , 49 ) and data repositories ( 50 ) that have driven improvements in predictive algorithms and will provide the data required for the next generation of AI-based informatic tools ( 25 ). Let’s use this same spirit to explore the immunopeptidome and illuminate its dark side as a community united in this purpose.…”
Section: Introductionmentioning
confidence: 99%